Sacral CSF-Venous Fistulas and Potential Imaging Techniques - Mark, I.T.; Morris, P.P.; Brinjikji, W.; Madhavan, A.A.; Cutsforth-Gregory, J.K.; Verdoorn, J.T. (American Journal of Neuroradiology, 2022)
SUMMARY: This is the first study to describe CSF-venous fistulas involving the sacrum, a location that may be underrecognized on the basis of current imaging techniques. We describe a delayed decubitus flat CT myelogram technique that may be useful to identify sacral CSF-venous fistulas.CTMCT myelographyCVFCSF-venous fistulaDAVFdural arteriovenous fistulaDECTdual-energy CTDSMdigital subtraction myelography